Baicalin effects on rats with spinal cord injury by anti‐inflammatory and regulating the serum metabolic disorder. Issue 9 (15th June 2018) - Kang, Shufeng; Liu, Shizhao; Li, Hongzhu; Wang, Dapeng; Qi, Xiangbei
Abstract: Baicalin had neuroprotective effects on inhibiting neuronal cell apoptosis induced by spinal cord ischemic injury. This study aimed to explore the protective effects of Baicalin on rats with spinal cord injury (SCI) and its mechanism of action. The recovery of spinal cord nerve function in rats was evaluated by the Basso, Beattie, and Bresnahan (BBB) score and the combine behavioral score (CBS). The expressions of cytokines tumor necrosis factor α (TNF‐α), interleukin‐1β (IL‐1β), and IL‐6 were detected by the enzyme‐linked immunosorbent assay method. Expressions of inflammation‐related proteins were detected by Western blot. Multivariate statistical analysis was performed for serum metabolites. The BBB and CBS score results showed that Baicalin had a certain improvement on rats with SCI. SCI symptoms were significantly improved in low‐dose and high‐dose groups. The levels of TNF‐α, IL‐1β, and IL‐6 in the SCI group were significantly increased. The expressions of NF‐κB p65, NF‐κB p50, p‐IκBα, and IKKα in the SCI group showed the opposite trend compared with the low‐dose and high‐dose groups. Compared with the sham group, glutamine, levels of 3‐OH‐butyrate, N ‐acetylaspartate, and glutathione were significantly reduced, and the levels of glutamate and betaine were significantly increased in the SCI group. When Baicalin was administered, the contents of glutamine synthase (GS) and glutaminase (GLS) were significantly reduced, indicating that Baicalin had the effect of improving GS and GLS. Baicalin has protective effects on improving SCI and lower extremity motor function, has a significant anti‐inflammatory effect, and regulates the serum metabolic disorder caused by SCI in rats. Abstract : Baicalin has protective effects on improving spinal cord injury (SCI) and lower extremity motor function, has a significant anti‐inflammatory effect, and regulates the serum metabolic disorder caused by SCI in rats.